Kinetic Modelling of Decyl Acetate Synthesis by Supercritical Biocatalysis - M. V. Oliveira (2009)
The synthesis of decyl acetate, by the transesterification reaction of vinyl acetate withdecanol, was studied using supercritical CO2 as solvent and immobilized Candida antarcticalipase B as catalyst (Novozym 435). The enzymatic content was determined for each particlesize of the catalyst, showing that the smallest particles have a larger specific amount ofenzyme and indicating that the enzyme is located in an external shell of the particle,following an egg-shell distribution, with an estimated thickness of ca. 60 µm, independentof the particle size. The reaction was enhanced by increasing the enzyme loading, theconcentration of vinyl acetate and the temperature; it was inhibited by excess of decanol andby increasing the pressure. A simplified model, based on the Ping-pong bi-bi mechanismwith competitive inhibition by the alcohol, was proposed for the transesterification of vinylacetate with decanol at 35 ºC and 100 bar, and it was found to be suitable to represent thekinetic data.